Memoirs of the life of Sir Samuel Romilly. edited by his sons. - Romilly, Samuel, 1757-1818 (Cambridge library collection., 2013)
A friend of Wilberforce and Bentham, Sir Samuel Romilly (1757-1818) combined considerable legal expertise with commitment to progressive political causes such as the abolition of the slave trade. During his time in Parliament - he was Solicitor General in Lord Grenville's 'Ministry of All the Talents' - he sought to lessen the archaic severity of English criminal law regarding corporal and capital punishment. Though he met with resistance, his efforts raised awareness and influenced later reforms. Compiled by his sons and published in 1840, this three-volume collection of autobiographical writings and varied correspondence illuminates the development of his outlook and the principles which guided him. Volume 1 includes Romilly's two-part narrative of his life from 1757 to 1789, letters about English affairs sent to his brother-in-law in Lausanne (1780-3), letters from eminent friends such as the French revolutionary Mirabeau (1783-7), and selected correspondence with the Genevan writer Étienne Dumont and others (1788-91).